Copper-based electro-catalytic material as well as preparation method and application thereof
By using multi-element doped copper-based nanowire electrocatalytic materials during the electrocatalytic CO2 reduction process, the existing copper-based catalysts have been solved, and efficient and stable ethylene preparation is achieved.
Patent Information
- Application Number
- CN202311393617.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-25
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-10-25
AI Technical Summary
The existing copper-based catalysts have low activity, low ethylene selectivity and poor stability during electrocatalytic CO2 reduction, especially under high current density, which can easily lead to catalyst agglomeration and rapid attenuation of performance.
By mixing the thiophenol ligand with the copper salt solution, a high-coordinated, multi-element doped copper-based nanowire precursor-metal organic frame material was formed. After calcination and electrochemical activation, multiple element-doped copper-based nanowires were prepared to form a stable copper-based electrocatalytic material.
The activity of the catalyst and ethylene selectivity are improved, the stability at high current density is enhanced, and the high ethylene Faraday efficiency can be maintained at 800mA/cm2 current density, and the efficiency is still maintained at 50% after 48 hours.
Smart Images

Figure CN119876994A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrocatalytic CO2 reduction, and in particular to a copper-based electrocatalytic material and a preparation method and application thereof. Background Art
[0002] Electrochemical catalytic reduction of CO2 to small organic molecules is one of the important ways to realize CO2 resource utilization, reduce the CO2 content in the atmosphere, and alleviate the "greenhouse effect". It is also an important link in establishing a new carbon resource balance system. The electrocatalytic CO2 reduction reaction involves a multi-electron transfer process, which puts forward new requirements for catalyst design. Copper is the only catalyst that can electrocatalyze the reduction of CO2 to generate C1 and C 2+ The metal of the product has important scientific significance for regulating its catalytic selectivity. At present, the research on Cu-based catalysts focuses on the influence of catalyst size, composition, exposed crystal surface and chemical valence on the catalytic performance of CO2 electro-reduction, but it is still not ideal to obtain catalysts with high selectivity and high catalytic activity. Therefore, seeking and developing efficient and stable catalysts, improving catalytic efficiency and optimizing product selectivity play an important role in the development of electrocatalytic CO2 reduction.
[0003] However, the copper-based nano-electrocatalyst materials obtained by the precipitation method or sacrificial template method commonly used at present have complex morphology of surface active components and variable crystal faces, which lead to poor ethylene selectivity. In the electrocatalytic process, the spatial structure of the above copper-based electrocatalyst materials is unstable, especially at higher current density (>500mAcm -2 ) under low temperature, catalyst agglomeration is likely to occur, leading to structural damage and rapid performance degradation.
[0004] CN112316965A discloses a method for preparing a laccase-copper phosphate nanoflower material, which belongs to the field of electrocatalysis technology. The invention dissolves laccase in a phosphate buffer solution and mixes it with ultrasound, adds a copper sulfate solution, allows it to stand, centrifuges to take out the lower layer of precipitation, washes it with ethanol, and vacuum dries it to obtain a laccase-copper phosphate La / Cu3(PO4)2 nanoflower.
[0005] CN103303962B discloses a method for preparing nano copper oxide by solid phase template method. Take equal amounts of copper salt and sodium carbonate and grind them separately, transfer them to the same mortar, add ligninamine and continue grinding in the mortar to obtain a mixture; the obtained mixture is ultrasonically cleaned with deionized water, centrifuged, the precipitate is cleaned with deionized water, then cleaned with anhydrous ethanol, and centrifuged; the separated solid is placed in a constant temperature drying oven for drying; finally, the dried solid is roasted at high temperature to obtain the nano copper oxide.
[0006] Therefore, developing efficient and stable catalysts, improving catalytic efficiency and optimizing product selectivity are of great strategic significance for the research on electrocatalytic CO2 reduction. Summary of the invention
[0007] The purpose of the present invention is to overcome the problems of low activity, low ethylene selectivity and poor stability of copper-based catalysts for electrocatalytic CO2 reduction in the prior art, and to provide an element-doped copper-based electrocatalytic material and its preparation method and application.
[0008] In order to achieve the above-mentioned object, the first aspect of the present invention provides a copper-based electrocatalytic material, wherein the copper-based electrocatalytic material comprises a plurality of element-doped copper-based nanowires.
[0009] A second aspect of the present invention provides a method for preparing a copper-based electrocatalytic material, wherein the preparation method comprises:
[0010] (1) mixing a solution containing a thiophenol ligand with a copper salt solution to obtain a suspension;
[0011] (2) subjecting the suspension to ultrasonic, heating, stirring and aging treatments, and then to centrifugation, washing and drying treatments to obtain a copper-based nanowire precursor;
[0012] (3) calcining the copper-based nanowire precursor;
[0013] (4) The calcined copper-based nanowire precursor is subjected to in-situ electrochemical activation treatment to obtain the copper-based electrocatalytic material.
[0014] The third aspect of the present invention provides the use of the copper-based electrocatalytic material in the electrocatalytic reduction reaction of carbon dioxide to produce ethylene.
[0015] Through the above technical scheme, thiophenol ligands are used as precipitants, and copper ions and thiophenol ligands are self-assembled to form a high-coordination, multi-element doped copper-based nanowire precursor-metal organic framework (MOF) material; thiophenol ligands contain a large amount of doping elements such as sulfur and oxygen, and under calcination conditions, they are pyrolyzed to form a multi-element doped copper-based catalytic material; finally, the copper-based catalytic material is obtained through electrochemical activation treatment, in-situ reduction and electrochemical reconstruction.
[0016] By controlling the process conditions (ultrasound, heating, stirring, aging, centrifugation and drying) during the preparation process, the prepared copper-based catalytic material has a nanowire structure with a length of 1-10 μm and a diameter of 20-200 nm; by controlling the calcination temperature, the multi-element doped copper-based nanowire precursor is fully pyrolyzed, and at the same time, the loss of doping elements and the occurrence of metal element sintering are reduced, thereby Figure 1 and Figure 4 It can be seen that the surface of the obtained copper-based nanowires is loose and porous, the sintering phenomenon is not obvious, and the specific surface area of the catalyst is 500-2000m 2 / g, pore volume 50-200cm3 The size and morphology of the copper-based catalyst of the present invention are conducive to promoting the electrocatalytic reduction of CO2 to produce ethylene and improving the selectivity of ethylene. The fluorine- and sulfur-doped copper-based catalyst prepared in Example 1 of the present invention has a current density of 800 mA / cm 2 At 1200 mA / cm 2 At a high current density, its ethylene Faraday efficiency is still 30.0%. By controlling the voltage or current value and the scanning number or activation time during electrochemical activation, the copper-based catalyst material is well activated and its electrocatalytic CO2 reduction performance is improved while the catalyst has good stability. The obtained copper-based catalyst is applied to electrocatalytic CO2 reduction. At a current density of 800 mA / cm 2 When the ethylene Faraday efficiency is 55.2%, and after 48 hours of use, it still has a relatively high ethylene Faraday efficiency (50%). It can be seen that the copper-based catalyst has good performance in electrocatalytic CO2 reduction to ethylene and can work efficiently and stably at a large current density.
[0017] The preparation process of the copper-based catalytic material is simple and effective, and does not require multi-step doping. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is a scanning electron microscope image of the copper-based electrocatalytic material prepared in Example 1;
[0019] Figure 2 This is a performance test comparison diagram of the copper-based electrocatalytic material and nano copper oxide prepared in Example 1;
[0020] Figure 3 This is a constant current stability test diagram of the copper-based electrocatalytic material prepared in Example 1;
[0021] Figure 4 is a transmission electron microscope image of the copper-based electrocatalyst material prepared in Example 1. DETAILED DESCRIPTION
[0022] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0023] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0024] A first aspect of the present invention provides a copper-based electrocatalytic material, wherein the copper-based electrocatalytic material comprises a plurality of element-doped copper-based nanowires.
[0025] The copper-based electrocatalytic material described in the present invention comprises a plurality of copper-based nanowires doped with the elements, and the plurality of copper-based nanowires doped with the elements are loosely stacked together to form the copper-based catalytic material. The plurality of copper-based nanowires doped with the elements have a nanostructure, and gaps are left between the nanowires, which increases the specific surface area and pore volume of the copper-based catalyst material, and is beneficial to improving the activity of the catalyst when used for electrocatalytic CO2 reduction to prepare ethylene. In addition, the doping elements in the copper-based nanowires doped with the elements exist inside and on the surface of the nanowires, which is beneficial to promote the generation of ethylene products; the doping elements on the surface of the copper-based nanowires doped with the elements are precipitated in large quantities during the reduction process, and some heteroatoms remaining on the subsurface or deeper levels affect the adsorption and generation process of the intermediates, so that part of the positively valenced Cu (Cu*) is retained on the catalyst surface, and the Cu* and Cu* in adjacent positions are not precipitated. 0 It is beneficial to the coupling between *CO intermediates to generate multi-carbon products, improving the ethylene selectivity in the electrocatalytic CO2 reduction reaction and the stability at high current density.
[0026] In the present invention, the copper-based electrocatalytic material can be prepared by the preparation method provided in the second aspect of the present invention.
[0027] According to the copper-based electrocatalytic material of the present invention, preferably, in the copper-based electrocatalytic material, the packing density of the plurality of copper-based nanowires doped with the element is 0.3-0.4 g / cm 3 .
[0028] In some embodiments of the present invention, in the copper-based electrocatalytic material, the packing density of the plurality of copper-based nanowires doped with the element is 0.35 g / cm 3 , 0.8g / cm 3 , 0.7g / cm 3 , 0.6g / cm 3 , 0.5g / cm 3 .
[0029] According to the present invention, in order to make the copper-based electrocatalytic material have a large specific surface area and pore volume and improve the activity of the catalyst in electrocatalytic CO2 reduction to produce ethylene, preferably, in the copper-based electrocatalytic material, the diameter of the element-doped copper-based nanowire is 20-200nm, the length is 1-10μm, the specific surface area is 1500-2000m 2 / g, pore volume is 150-200cm 3 / g.
[0030] In some embodiments of the present invention, preferably, in the copper-based electrocatalytic material, the diameters of the element-doped copper-based nanowires are 20-50 nm, 60-100 nm, 100-200 nm, 150-200 nm, respectively, the lengths are 1-10 μm, respectively, and the specific surface area is 2000 m 2 / g、1200m 2 / g、800m 2 / g、500m 2 / g、1500m 2 / g, pore volume is 200cm 3 / g, 120cm 3 / g, 80cm 3 / g, 50cm 3 / g, 150cm 3 / g.
[0031] According to the copper-based electrocatalytic material of the present invention, preferably, in the element-doped copper-based nanowires, the copper element is in the form of Cu 2+ , Cu + , Cu 0 exists in one or more forms.
[0032] In some embodiments of the present invention, preferably, in the element-doped copper-based nanowires, the copper element is mainly in the form of Cu 2+ , Cu + Cu 0 exists in the form of.
[0033] According to the preparation method of the second aspect of the present invention, specifically, when the nanowire precursor formed by self-assembly of the metal-organic framework material is calcined in air, the doping element is partially lost, and most of the copper element is in the form of Cu 2+ When sintered under nitrogen, less doping elements are lost, and most of the copper element is in the form of Cu + When calcined under hydrogen, most of the doping elements are lost, and most of the copper element is in the form of Cu 0 In addition, when calcined at different temperatures under the same atmosphere, the components of the catalyst also differ to a certain extent.
[0034] The present invention uses surface enhanced Raman spectroscopy to detect the existing form of the copper element in the element-doped copper-based nanowires.
[0035] According to the copper-based electrocatalytic material of the present invention, preferably, in the element-doped copper-based nanowires, the doping element is selected from non-metallic elements, preferably selected from one or more of S, F, Br, N, and O.
[0036] In some embodiments of the present invention, preferably, in the element-doped copper-based nanowires, the doping elements are F and S, Br and S, F, Br, N and S, S, respectively.
[0037] According to the present invention, in order to make the copper-based electrocatalytic material have better activity in electrocatalytic CO2 reduction to produce ethylene, ethylene selectivity and stability under high current density, preferably, in the element-doped copper-based nanowires, the content of the doping element is 0.1-10wt%.
[0038] In the present invention, the composition and structure of the copper-based electrocatalytic material can be determined by scanning electron microscopy, inductively coupled plasma spectroscopy and BET specific surface area test method, and can also be determined by the feeding amount of each material in the preparation process.
[0039] A second aspect of the present invention provides a method for preparing a copper-based electrocatalytic material, wherein the method comprises:
[0040] (1) mixing a solution containing a thiophenol ligand with a copper salt solution to obtain a suspension;
[0041] (2) subjecting the suspension to ultrasonic, heating, stirring and aging treatments, and then to centrifugation, washing and drying treatments to obtain a copper-based nanowire precursor;
[0042] (3) calcining the copper-based nanowire precursor;
[0043] (4) The calcined copper-based nanowire precursor is subjected to in-situ electrochemical activation treatment to obtain the copper-based electrocatalytic material.
[0044] According to the preparation method of the present invention, thiophenol ligands are used as precipitants, and copper ions and thiophenol ligands are self-assembled to form a highly coordinated, multi-element doped copper-based nanowire precursor-metal organic framework (MOF) material; thiophenol ligands contain a large amount of doping elements such as sulfur and oxygen, and under calcination conditions, they are pyrolyzed to form a multi-element doped copper-based catalytic material; finally, the copper-based catalytic material is in situ reduced and electrochemically reconstructed through electrochemical activation treatment. According to the above statement, the copper-based electrocatalytic material prepared by the preparation method of the present invention includes a plurality of copper-based nanowires doped with the elements, and the plurality of copper-based nanowires doped with the elements are loosely stacked together to form the copper-based catalytic material. When used for electrocatalytic CO2 reduction to prepare ethylene, it is beneficial to improve the activity of the catalyst, ethylene selectivity and stability at a large current density.
[0045] According to the preparation method of the present invention, preferably, in the step (1), the copper salt is selected from one or more of copper chloride, copper nitrate and copper sulfate;
[0046] According to the present invention, in order to make the copper salt and the ligand self-assemble into a nanowire structure after coordination, and to make the copper salt and the ligand have spatial stability and not easy to agglomerate, preferably, in the step (1), the molar concentration of the copper salt solution is 1-100mmol / L.
[0047] More preferably, the molar concentration of the copper salt solution is 37.2-100 mmol / L.
[0048] In some embodiments of the present invention, in step (1), the molar concentration of the copper salt solution is 37.2 mmol / L, 10 mmol / L, 90 mmol / L, 100 mmol / L and 50 mmol / L.
[0049] According to the preparation method of the present invention, preferably, in the step (1), the thiophenol ligand is selected from one or more of 4-bromothiophenol, 4-fluorothiophenol, 4-aminothiophenol and 4-hydroxythiophenol.
[0050] According to the present invention, in order to allow the thiophenol ligand to form a high coordination structure with the copper ion, to form an active site that is beneficial to CC coupling, and to avoid local agglomeration during the dropwise addition process to form large particles and lose the microscopic morphology advantage, preferably, in the step (1), the molar concentration of the ligand solution is 100-1000mmol / L.
[0051] More preferably, the molar concentration of the ligand solution is 100-500 mmol / L.
[0052] In some embodiments of the present invention, in step (1), the molar concentration of the ligand solution is 264 mmol / L, 100 mmol / L, 300 mmol / L and 500 mmol / L.
[0053] According to the preparation method of the present invention, preferably, in the step (1), the ligand solution and the copper salt solution are mixed in the following manner: a solution containing thiophenol ligands is added dropwise to the copper salt solution to obtain a suspension; or a solution containing thiophenol ligands is directly mixed with the copper salt solution, and then stirred to obtain a suspension.
[0054] According to the present invention, there is no particular limitation on the solvent in the solution containing the thiophenol ligand and the copper salt solution, as long as they are dissolved. Preferably, the solvent is selected from one or more of ethanol, ether and carbon disulfide.
[0055] According to the preparation method of the present invention, preferably, in the step (1), the mixing volume ratio of the copper salt solution to the ligand solution is 0.5:1-2:1.
[0056] In some embodiments of the present invention, preferably, in the step (1), the mixing volume ratio of the copper salt solution to the ligand solution is 1:1.
[0057] According to the preparation method of the present invention, preferably, in the step (2), the ultrasonic power is 50-500W, the ultrasonic time is 0.01-2h, the heating temperature is 60-100°C, the stirring rate is 100-1000rpm, the aging time is 0.01-12h, the centrifugal rate is 2000-10000rpm, and the drying temperature is 50-100°C.
[0058] According to the present invention, in order to control the length and diameter of the element-doped copper-based nanowires contained in the copper-based electrocatalytic material and ensure a higher product yield, preferably, in the step (2), the ultrasonic power is 500 W, the ultrasonic time is 1 h, the heating temperature is 60-80 ° C, the stirring rate is 400-800 rpm, the aging time is 1-12 h, the centrifugal rate is 8000 rpm, and the drying temperature is 60-90 ° C.
[0059] In some embodiments of the present invention, preferably, in step (2), the ultrasonic power is 500 W, 200 W, and 250 W, respectively; the ultrasonic time is 1 h, 2 h, and 1.5 h, respectively; the heating temperature is 80°C, 90°C, 70°C, and 60°C; the stirring rate is 400 rpm, 800 rpm, 600 rpm, and 700 rpm; the aging time is 1 h, 6 h, and 12 h; the centrifugal rate is 8000 rpm, 10000 rpm, and 5000 rpm; and the drying temperature is 60°C, 90°C, and 50°C.
[0060] According to the preparation method of the present invention, in the step (2), the washing is performed by alternating washing with water and ethanol.
[0061] According to the preparation method of the present invention, preferably, in the step (3), the calcination temperature is 400-1000°C, the calcination time is 1-5h, the heating rate is 0.5-10°C / min, and the calcination atmosphere is selected from one or more of air, nitrogen and hydrogen.
[0062] According to the present invention, in order to fully pyrolyze the multi-element doped copper-based nanowire precursor and reduce the loss of doping elements and the occurrence of metal element sintering, preferably, in the step (3), the calcination temperature is 600-700°C, the calcination time is 2-4h, and the heating rate is 0.5-2°C / min.
[0063] In some embodiments of the present invention, preferably, in the step (3), the calcination temperature is 700°C, 900°C, 600°C, the calcination time is 2h, 4h, 5h, 1h, and the heating rate is 2°C / min, 5°C / min, 10°C / min, 0.5°C / min.
[0064] According to the preparation method of the present invention, preferably, in the step (4), the electrochemical activation treatment method is selected from one or more of linear sweep voltammetry, cyclic voltammetry, constant current method and constant voltage method.
[0065] According to the present invention, in order to effectively activate the calcined copper-based nanowire precursor and ensure the stability of the obtained copper-based catalytic material, preferably, in the step (4), when the linear sweep voltammetry and cyclic voltammetry are used, a three-electrode system is used, the voltage is relative to the reversible hydrogen electrode (VS.RHE), the voltage range is between -2.5 and 0V, and the scan or cycle is 1-80 times.
[0066] More preferably, when the linear sweep voltammetry and cyclic voltammetry are used, the voltage range is between -1.8 and -1.2 V, and the scan or cycle is performed 40 times.
[0067] Preferably, in step (4), when the constant current method is used, the current density is between -10 and -1500 mA / cm 2 The reaction time is 0.05-3h.
[0068] More preferably, when the constant current method is used, the current density is -100 mA / cm 2 , the reaction time is 5min.
[0069] Preferably, in step (4), when the constant voltage method is adopted, the voltage range is between -3.5 and -1.5 V, and the reaction time is 0.05-3 h.
[0070] More preferably, when the constant voltage method is adopted, the voltage is -1.6 V and the reaction time is 5 min.
[0071] According to the present invention, in the step (4), preferably, the calcined solid is coated on the electrode material and then electrochemical in-situ activation is performed.
[0072] According to the present invention, in the step (4), more preferably, the calcined solid is coated on a carbon electrode material and then electrochemically activated in situ; specifically, the carbon electrode material is selected from carbon paper, carbon felt or carbon cloth.
[0073] In some embodiments of the present invention, preferably, the carbon electrode material is a carbon paper electrode.
[0074] The third aspect of the present invention provides the use of the copper-based electrocatalytic material in the electrocatalytic reduction reaction of carbon dioxide to produce ethylene.
[0075] The copper-based catalyst obtained by the present invention was applied to electrocatalytic CO2 reduction at a current density of 800 mA / cm 2 When the copper-based catalyst has an ethylene Faradaic efficiency of 55.2%, even at 1200 mA / cm 2 At a high current density of 800 mA / cm 2 At the current density, after 48 hours of electrocatalytic reduction, the ethylene Faraday efficiency of the copper-based catalyst did not decrease significantly, and was still about 50%. It can be seen that the copper-based catalyst has good performance in electrocatalytic CO2 reduction to ethylene, and can work efficiently and stably at a large current density.
[0076] The following examples are used to illustrate the technical solutions of the present invention, wherein the raw materials and reagents used are commercially available, and the room temperature refers to 15-35°C.
[0077] Cupric chloride dihydrate, purity AR (≥99.0%, Shanghai test), purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0078] Copper nitrate trihydrate, purity AR (≥99.0%, Shanghai test), purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0079] Copper sulfate pentahydrate, purity AR (≥99.0%, Shanghai test), purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0080] 4-Bromothiophenol, purity 97%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0081] 4-Fluorobenzenethiol, purity 98%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0082] 4-Aminothiophenol, purity ≥98% (GC), was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0083] 4-Hydroxythiophenol, purity 97%, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0084] Example 1
[0085] Preparation of fluorine and sulfur doped copper-based catalytic materials
[0086] The method comprises the following steps: preparing a copper nitrate ethanol solution with a molar concentration of 37.2 mmol / L and preparing a 4-fluorothiophenol ethanol solution with a molar concentration of 264 mmol / L; adding an equal volume of the 4-fluorothiophenol / ethanol solution dropwise to the copper nitrate / ethanol solution to obtain a suspension; ultrasonicating (500 W) for 1 hour, heating to 80° C., aging at a stirring rate of 400 rpm for 1 hour, washing with water and ethanol alternately at a centrifugal speed of 8000 rpm, and drying at a temperature of 60° C.; calcining the dried solid at 700° C. in an air atmosphere for 2 hours, wherein the heating rate is 2° C. / min; coating the calcined solid on a carbon paper electrode, and performing electrochemical in-situ activation by a constant current method, wherein the current during the electrochemical in-situ activation treatment is -100 mA / cm 2 , the treatment time is 5 minutes, and fluorine and sulfur doped copper-based catalytic materials are obtained.
[0087] The fluorine- and sulfur-doped copper-based catalytic materials were subjected to electron microscopy scanning and BET specific surface area measurement. Figure 1 The scanning electron microscope image shown in FIG. 1 shows that the fluorine- and sulfur-doped copper-based catalytic material comprises a plurality of copper-based nanowires, and the packing density of the plurality of copper-based nanowires doped with the elements is 0.35 g / cm 3 ; The diameter of the nanowire is 20-50nm and the length is 1-10μm; In addition, Figure 4 The transmission electron microscope image shown in the figure shows that the surface of the nanowire is loose and porous, with a specific surface area of 2000m 2 / g, pore volume is 200cm 3 / g; the content of doping elements is 5wt%.
[0088] Surface enhanced Raman spectroscopy was used to detect the fluorine- and sulfur-doped copper-based catalytic material prepared in Example 1. From the test results, it can be seen that the copper element is mainly in the form of Cu 2+ exists in the form of.
[0089] The fluorine- and sulfur-doped copper-based catalytic material prepared in Example 1 was subjected to an electrochemical performance test for electrocatalytic CO2 reduction to ethylene in a flow electrolysis cell device, with pure CO2 as the raw material, a flow rate of 30 mL / min, and normal temperature and pressure. The results are shown in 2. Figure 3 shown.
[0090] Figure 2 This is a performance test comparison chart of fluorine- and sulfur-doped copper-based catalytic materials and nano copper oxide. It can be seen from the figure that at a current density of 800mA / cm 2 When the fluorine and sulfur doped copper-based electrocatalyst material has an ethylene Faraday efficiency of 55.2%, and at 1200 mA / cm 2At a high current density, its ethylene Faraday efficiency is still 30.0%. This shows that the copper-based catalytic material doped with fluorine and sulfur has good electrocatalytic performance in CO2 reduction to ethylene and has good ethylene selectivity. In addition, the copper-based electrocatalytic material doped with multiple elements has a good electrocatalytic performance in CO2 reduction to ethylene at a current density of 800 mA / cm 2 At 1200 mA / cm 2 At a high current density, its hydrogen Faraday efficiency is 54.8%.
[0091] Figure 3 This is a constant current stability test diagram of fluorine and sulfur doped copper-based catalyst materials. It can be seen from the figure that at 800mA / cm 2 Under the current density, there was no significant increase in the overpotential after 48 hours of testing, and the Faraday efficiency of ethylene did not decrease significantly, still at about 50%, indicating that the fluorine- and sulfur-doped copper-based catalytic material has excellent stability.
[0092] Example 2
[0093] Preparation of bromine and sulfur-doped copper-based catalytic materials
[0094] The invention discloses a method for preparing a copper nitrate ethanol solution with a molar concentration of 10 mmol / L and a 4-bromothiophenol ethanol solution with a molar concentration of 100 mmol / L; adding an equal volume of the 4-bromothiophenol / ethanol solution dropwise to the copper nitrate / ethanol solution to obtain a suspension; ultrasonicating (200 W) for 2 hours, heating to 90°C, and aging for 6 hours at a stirring rate of 800 rpm; washing with water and ethanol alternately at a centrifugal speed of 10000 rpm, and drying at 90°C; calcining the dried solid at 700°C for 4 hours in a nitrogen atmosphere, wherein the heating rate is 5°C / min; coating the calcined solid on a carbon paper electrode, and performing electrochemical in-situ activation by a constant current method, wherein the current during the electrochemical in-situ activation treatment is -200 mA / cm 2 , the treatment time is 2 min. A bromine and sulfur doped copper-based catalytic material is obtained.
[0095] Electron microscope scanning and BET specific surface area measurement were performed on the bromine- and sulfur-doped copper-based catalytic materials, respectively. It can be seen that the bromine- and sulfur-doped copper-based catalytic material prepared in Example 2 comprises a plurality of copper-based nanowires, and the packing density of the plurality of copper-based nanowires doped with the elements is 0.8 g / cm 3 The diameter of the nanowire is 60-100nm and the length is 1-10μm. In addition, the surface of the nanowire is loose and porous, with a specific surface area of 1200m 2 / g, pore volume 120cm 3 / g.
[0096] Surface enhanced Raman spectroscopy was used to detect the bromine and sulfur doped copper-based catalytic material prepared in Example 2. From the test results, it can be seen that the copper element is mainly in the form of Cu + exists in the form of.
[0097] The bromine- and sulfur-doped copper-based catalyst material prepared in Example 2 was subjected to an electrochemical performance test for electrocatalytic CO2 reduction to ethylene in a flow electrolysis cell device, and the test conditions were the same as those in Example 1. At a current density of 800 mA / cm 2 When the bromine and sulfur doped copper-based catalyst material has an ethylene Faraday efficiency of 20.3% and a hydrogen Faraday efficiency of 55.6%, the 1200 mA / cm 2 At high current density, its ethylene Faraday efficiency is 9.1% and hydrogen Faraday efficiency is 80.7%. 2 Under the current density, there is no obvious increase in overpotential after 2h of testing, and the Faraday efficiency of ethylene does not decrease significantly.
[0098] Example 3
[0099] Preparation of copper-based catalytic materials doped with bromine, fluorine, nitrogen and sulfur
[0100] A mixed ethanol solution containing copper nitrate, copper sulfate and copper chloride is prepared, and the molar concentration of each copper salt is 30mmol / L. A mixed ethanol solution containing 4-bromothiophenol, 4-fluorothiophenol and 4-aminothiophenol ligands is prepared, and the molar concentration of each ligand is 100mmol / L; an equal volume of the mixed thiophenol ligand / ethanol solution is added dropwise to the mixed copper salt / ethanol solution to obtain a suspension; ultrasonic (500W) for 1.5 hours, heated to 70°C, aged for 12 hours at a stirring rate of 600rpm, washed alternately with water and ethanol at a centrifugal speed of 5000rpm, and dried at 50°C; the dried solid is calcined at 900°C for 5 hours in a hydrogen / nitrogen mixed atmosphere, wherein the heating rate is 10°C / min; the calcined solid is coated on a carbon paper electrode, and electrochemical in-situ activation is performed by a constant current method, wherein the current during the electrochemical in-situ activation treatment is -100mA / cm 2 The treatment time is 10 min. A copper-based catalytic material doped with bromine, fluorine, nitrogen and sulfur is obtained.
[0101] Electron microscope scanning and BET specific surface area measurement were performed on the copper-based catalytic materials doped with bromine, fluorine, nitrogen and sulfur, respectively. It can be seen that the copper-based catalytic materials doped with bromine, fluorine, nitrogen and sulfur prepared in Example 3 contain a plurality of copper-based nanowires, and the packing density of the plurality of copper-based nanowires doped with the elements is 0.7 g / cm 3 The diameter of the nanowire is 100-200nm and the length is 1-10μm. In addition, the surface of the nanowire is loose and porous, with a specific surface area of 800m2 / g, pore volume 80cm 3 / g.
[0102] Surface enhanced Raman spectroscopy was used to detect the copper-based catalytic material doped with bromine, fluorine, nitrogen and sulfur prepared in Example 3. From the test results, it can be seen that the copper element is mainly in the form of Cu 0 exists in the form of.
[0103] The copper-based catalytic material doped with bromine, fluorine, nitrogen and sulfur prepared in Example 3 was subjected to electrochemical performance test of electrocatalytic CO2 reduction to ethylene in a flow electrolysis cell device, and the test conditions were the same as those in Example 1. At a current density of 800 mA / cm 2 When the bromine, fluorine, nitrogen, and sulfur doped copper-based catalyst material has an ethylene Faraday efficiency of 27.3% and a hydrogen Faraday efficiency of 50.9%, the 1200 mA / cm 2 At high current density, its ethylene Faraday efficiency is 6.1% and hydrogen Faraday efficiency is 90.6%. 2 Under the current density, after testing for 10 hours, there is no obvious increase in overpotential, and the Faraday efficiency of ethylene does not decrease significantly.
[0104] Example 4
[0105] Preparation of sulfur-doped copper-based catalytic materials
[0106] Prepare a copper nitrate ethanol-carbon disulfide mixed solution with a molar concentration of 100mmol / L, prepare a 4-hydroxythiophenol ethanol-carbon disulfide mixed solution with a molar concentration of 500mmol / L; add an equal volume of 4-hydroxythiophenol / ethanol-carbon disulfide mixed solution dropwise to the copper nitrate / ethanol-carbon disulfide mixed solution to obtain a suspension; ultrasonicate (500W) for 1h, heat to 80°C, and age for 12h at a stirring rate of 700rpm; wash alternately with water and ethanol at a centrifugal speed of 8000rpm, and dry at 60°C; calcine the dried solid at 700°C in an air atmosphere for 4h, wherein the heating rate is 0.5°C / min; coat the calcined solid on a carbon paper electrode, and perform electrochemical in-situ activation by cyclic voltammetry, wherein the voltage range during the electrochemical in-situ activation treatment is -2.5-0V, and the cycle is 80 times. A sulfur-doped copper-based catalytic material is obtained.
[0107] Electron microscope scanning and BET specific surface area measurement were performed on the sulfur-doped copper-based catalytic material respectively. It can be seen that the oxygen- and sulfur-doped copper-based catalytic material prepared in Example 4 comprises a plurality of copper-based nanowires, and the packing density of the plurality of copper-based nanowires doped with the element is 0.6 g / cm 3The diameter of the nanowire is 150-200nm and the length is 1-10μm. In addition, the surface of the nanowire is loose and porous, with a specific surface area of 500m 2 / g, pore volume 50cm 3 / g.
[0108] The sulfur-doped copper-based catalytic material prepared in Example 4 was tested by surface enhanced Raman spectroscopy. From the test results, it can be seen that the copper element is mainly in the form of Cu 2+ exists in the form of.
[0109] The sulfur-doped copper-based catalytic material prepared in Example 4 was subjected to electrochemical performance test of electrocatalytic CO2 reduction to ethylene in a flow electrolysis cell device, and the test conditions were the same as those in Example 1. At a current density of 800 mA / cm 2 When the sulfur-doped copper-based catalyst material has an ethylene Faraday efficiency of 30.9% and a hydrogen Faraday efficiency of 43.6%, the catalytic efficiency of sulfur-doped copper-based catalyst material is 1200 mA / cm 2 At high current density, its ethylene Faraday efficiency is 14.3% and hydrogen Faraday efficiency is 76.3%. 2 Under the current density, after testing for 1h, there is no obvious increase in overpotential and no obvious decrease in the Faraday efficiency of ethylene.
[0110] Example 5
[0111] Preparation of fluorine and sulfur doped copper-based catalytic materials
[0112] The invention discloses a method for preparing a copper nitrate ethanol solution with a molar concentration of 50 mmol / L and a 4-fluorothiophenol ethanol solution with a molar concentration of 100 mmol / L; adding an equal volume of the 4-fluorothiophenol / ethanol solution dropwise into the copper nitrate / ethanol solution to obtain a suspension; ultrasonicating (250 W) for 1 hour, heating to 60°C, and aging for 1 hour at a stirring rate of 800 rpm; washing with water and ethanol alternately at a centrifugal speed of 8000 rpm, and drying at a temperature of 90°C; calcining the dried solid at 600°C in a hydrogen atmosphere for 1 hour, wherein the heating rate is 2°C / min; coating the calcined solid on a carbon paper electrode, and performing electrochemical in-situ activation by a constant current method and a constant voltage method, wherein the current during the electrochemical in-situ treatment is -200 mA / cm 2 , treatment time is 2min; voltage is -1.6V, time is 0.5h. Fluorine and sulfur doped copper-based catalytic materials are obtained.
[0113] Electron microscope scanning and BET specific surface area measurement were performed on the fluorine- and sulfur-doped copper-based catalytic materials respectively. It can be seen that the fluorine- and sulfur-doped copper-based catalytic material prepared in Example 5 comprises a plurality of copper-based nanowires, and the packing density of the plurality of copper-based nanowires doped with the elements is 0.5 g / cm3 The diameter of the nanowire is 60-100nm and the length is 1-10μm. In addition, the surface of the nanowire is loose and porous, with a specific surface area of 1500m 2 / g, pore volume 150cm 3 / g.
[0114] Surface enhanced Raman spectroscopy was used to detect the fluorine- and sulfur-doped copper-based catalytic material prepared in Example 5. From the test results, it can be seen that the copper element is mainly in the form of Cu 0 exists in the form of.
[0115] The fluorine- and sulfur-doped copper-based catalytic material prepared in Example 5 was subjected to an electrochemical performance test for electrocatalytic CO2 reduction to ethylene in a flow electrolysis cell device, and the test conditions were the same as those in Example 1. At a current density of 800 mA / cm 2 When the fluorine and sulfur doped copper-based catalyst material has an ethylene Faraday efficiency of 40.2% and a hydrogen Faraday efficiency of 44.9%, the Faraday efficiency of 1200 mA / cm 2 At high current density, its ethylene Faraday efficiency is 3.1% and hydrogen Faraday efficiency is 84.7%. 2 Under the current density, after testing for 0.5h, its overpotential did not increase significantly, and the Faraday efficiency of ethylene did not decrease significantly.
[0116] It can be seen from the above examples that the preferred embodiment of the present invention can prepare a multi-element doped copper-based nanowire electrocatalytic material, which has a nanostructure and has gaps between the nanowires, increasing the specific surface area and pore volume of the copper-based catalyst material, which is beneficial to improving the activity of the catalyst when used for electrocatalytic CO2 reduction to produce ethylene. In addition, the doping elements in the element-doped copper-based nanowires are present inside and on the surface of the nanowires, which is beneficial to promote the production of ethylene products; the doping elements on the surface of the element-doped copper-based nanowires are precipitated in large quantities during the reduction process, and some heteroatoms remaining on the subsurface or deeper layers have an impact on the adsorption and production process of the intermediates, so that part of the positively charged Cu (Cu*) is retained on the catalyst surface, and the Cu* and Cu* in adjacent positions are not directly related to each other. 0 It is beneficial to the coupling between *CO intermediates to generate multi-carbon products, improving the ethylene selectivity in the electrocatalytic CO2 reduction reaction and the stability at high current density.
[0117] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various specific technical features in any appropriate manner, but these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A copper-based electrocatalytic material, characterized in that: The copper-based electrocatalytic material comprises a plurality of element-doped copper-based nanowires.
2. The copper-based electrocatalytic material according to claim 1, wherein: In the copper-based electrocatalytic material, the packing density of the plurality of copper-based nanowires doped with the element is 0.3-1 g / cm 3 .
3. The copper-based electrocatalytic material according to claim 1 or 2, wherein: The element-doped copper-based nanowire has a diameter of 20-200 nm, a length of 1-10 μm, and a specific surface area of 500-2000 m 2 / g, pore volume 50-200cm 3 / g.
4. The copper-based electrocatalytic material according to any one of claims 1 to 3, wherein: The copper element in the element-doped copper-based nanowire is Cu 2+ , Cu + , Cu 0 One or more forms of exist.
5. The copper-based electrocatalytic material according to any one of claims 1 to 4, wherein: The doping elements in the element-doped copper-based nanowires are selected from non-metallic elements, preferably selected from one or more of S, F, Br, N, and O.
6. The copper-based electrocatalytic material according to any one of claims 1 to 5, wherein: In the element-doped copper-based nanowires, the content of the doping element is 0.1-10 wt %.
7. A method for preparing a copper-based electrocatalytic material, characterized in that: The preparation method comprises: (1) mixing a solution containing a thiophenol ligand with a copper salt solution to obtain a suspension; (2) subjecting the suspension to ultrasonic, heating, stirring and aging treatments, and then to centrifugation, washing and drying treatments to obtain a copper-based nanowire precursor; (3) calcining the copper-based nanowire precursor; (4) The calcined copper-based nanowire precursor is subjected to in-situ electrochemical activation treatment to obtain the copper-based electrocatalytic material.
8. The preparation method according to claim 7, wherein: In step (1), the copper salt is selected from one or more of copper chloride, copper nitrate and copper sulfate; Preferably, the molar concentration of the copper salt solution is 1-100 mmol / L.
9. The preparation method according to claim 7 or 8, wherein: The molar concentration of the copper salt solution is 37.2-100 mmol / L.
10. The preparation method according to any one of claims 7 to 9, wherein: In step (1), the thiophenol ligand is selected from one or more of 4-bromothiophenol, 4-fluorothiophenol, 4-aminothiophenol and 4-hydroxythiophenol; Preferably, the molar concentration of the ligand solution is 100-1000 mmol / L.
11. The preparation method according to any one of claims 7 to 10, wherein: The molar concentration of the ligand solution is 100-500 mmol / L.
12. The preparation method according to any one of claims 7 to 11, wherein: In step (1), the mixing volume ratio of the copper salt solution to the ligand solution is 0.2-5:
1.
13. The preparation method according to any one of claims 7 to 12, wherein: In step (2), the ultrasonic power is 50-500W, the ultrasonic time is 0.01-2h, the heating temperature is 60-100°C, the stirring rate is 100-1000rpm, the aging time is 0.01-12h, the centrifugal rate is 2000-10000rpm, the washing is performed by alternating deionized water and ethanol, and the drying temperature is 50-100°C.
14. The preparation method according to any one of claims 7 to 13, wherein: In step (3), the calcination temperature is 400-1000° C., the calcination time is 1-5 h, the heating rate is 0.5-10° C. / min, and the calcination atmosphere is selected from one or more of air, nitrogen and hydrogen.
15. The preparation method according to any one of claims 7 to 14, wherein: The calcination temperature is 600-700° C., the calcination time is 2-4 hours, and the heating rate is 0.5-2° C. / min.
16. The preparation method according to any one of claims 7 to 15, wherein: In step (4), the electrochemical activation treatment method is selected from one or more of linear sweep voltammetry, cyclic voltammetry, constant current method and constant voltage method.
17. The preparation method according to claim 16, wherein: The voltage range of the linear sweep voltammetry and cyclic voltammetry is -2.5 to 0 V, and the scan or cycle is 1 to 80 times; The current density of the constant current method is -10 to -1500 mA / cm 2 , reaction time is 0.05-3h; The voltage of the constant voltage method is -1.5 to -3.5 V, and the reaction time is 0.05-3 h.
18. Use of the copper-based electrocatalytic material according to any one of claims 1 to 6 or the copper-based electrocatalytic material prepared by the preparation method according to any one of claims 7 to 17 in the electrocatalytic reduction reaction of carbon dioxide to produce ethylene.
Citation Information
Patent Citations
Copper-based catalyst, and preparation method and application thereof
CN111659394A
Non-metal doped copper-based catalytic material for electrocatalytic reduction of carbon dioxide as well as preparation method and application of non-metal doped copper-based catalytic material
CN115710724A
Nitrogen / sulfur co-doped porous carbon loaded zinc monatomic / metallic copper series catalyst as well as preparation method and application of nitrogen / sulfur co-doped porous carbon loaded zinc monatomic / metallic copper series catalyst
CN115896848A
Method for preparing fe@cumoo 4NWA / cu catalyst and application
WO2023284064A1
Cited By
Synthetic method for in-situ construction of Cu < + > / Cu0 interface nano-catalyst based on heteroatom induction
CN120250063A
Benzothiadiazole modified monatomic zirconium doped metal copper electrode material and preparation method and application thereof
CN120505663A
A benzothiadiazole modified single-atom zirconium-doped copper electrode material, a preparation method therefor, and an application thereof
CN120505663B